Phytohormone combined with nitrogen stress promoted carbon conversion in CO2 chemical absorption and microalgae conversion system - Hu, Zhan; Wang, Dantong; Li, Pengcheng; Hou, Yaoqi; Chen, Guanyi; Song, Chunfeng (Frontiers in Bioengineering and Biotechnology, 2025)
The CO2 chemical absorption and microalgae conversion (CAMC) system can achieve low-energy consumption CO2 capture and resource utilization, but the study on enhancing the synthesis of high-value products has been overlooked. In this study, the coupling strategy of nitrogen stress and exogenous phytohormones was applied to induce high-value products accumulation of Dunaliella salina in CAMC system, and the potential mechanism was also discussed. The results showed that phytohormones could promote D. salina growth by alleviating the oxidative damage under nitrogen limited treatment, especially in gibberellin (GA) group, and the biomass increased by 10.24%. In addition, phytohormones combined nitrogen limited changed carbon flow, directing more carbon to polysaccharose synthesis, supplementation with GA under nitrogen-limited conditions resulted in a 1.65-fold increase in polysaccharide content in D. salina compared to the control. Furthermore, supplementation with GA under nitrogen-limited conditions enhanced the accumulation of β-carotene, and the β-carotene yield and content were 18.52% and 14.46% higher than control. This study suggested that GA could further affect carbon metabolism and products synthesis of D. salina under nitrogen stress, and provided a possible insight in improving the production of economical metabolites in CAMC system.